Separate the variables by moving all the y terms to one side of the equation and all the x terms to the other side:
"x(y^2-1)dy=-y(y^2+1)dx""(y^2-1)dy=-\\frac{y(y^2+1)dx}{x}""\\frac{y^2-1}{y(y^2+1)}dy=-\\frac{dx}{x}" Integrate both sides of the equation :
"\\int\\frac{y^2-1}{y(y^2+1)}dy=-\\int\\frac{dx}{x}"Solve the first integral using partial fractions:
"\\frac{y^2-1}{y(y^2+1)}=\\frac{A}{y}+\\frac{By+C}{y^2+1}=\\frac{A(y^2+1)+(By+C)y}{y(y^2+1)}" Then
"y^2-1=A(y^2+1)+(By+C)y""y^2-1=Ay^2+A+By^2 +Cy""y^2-1=(A+B)y^2+A+Cy""\\begin{cases} A+B=1 \\\\ A=-1 \\\\ C=0 \\end{cases}""\\begin{cases} A=-1\\\\ B=2 \\\\C=0 \\end{cases}" Hence
"\\int\\frac{y^2-1}{y(y^2+1)}dy=\\int(-\\frac{1}{y}+\\frac{2y}{y^2+1})dy="
"=-\\int\\frac{dy}{y}+\\int\\frac{d(y^2+1)}{y^2+1}=-ln y+ln (y^2+1)" Then the solution of the differential equation is:
"-ln y+ln (y^2+1)=-\\int\\frac{dx}{x}""ln\\frac{y^2+1}{y}=-ln{x}+ln{C}""ln\\frac{y^2+1}{y}=ln\\frac{C}{x}""\\frac{y^2+1}{y}=\\frac{C}{x}" Solve for y:
"y^2+1=\\frac{C}{x}y""y^2-\\frac{C}{x}y+1=0"
"y=\\frac{\\frac{C}{x}\\pm\\sqrt{\\frac{C^2}{x^2}-4}}{2}""y=\\frac{\\frac{C}{x}\\pm\\frac{\\sqrt{C^2-4x^2}}{x}}{2}""y=\\frac{C\\pm\\sqrt{C^2-4x^2}}{2x}"
Answer: "y=\\frac{C\\pm\\sqrt{C^2-4x^2}}{2x}"
Comments
Leave a comment